Structure and Luminescence Properties of Y\(_2\)O\(_3\): Eu\(^{3+}\) Nanophosphors (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Europium trivalent (Eu\( ^{3+}\), 2%) doped Y\(_2\)O\(_3\) nanophosphors were synthesized by solgel method and annealed at temperature 600 \(^°\)C and 900 \(^°\)C. The phosphors were characterized by XRD, FTIR, UV-visible and PL spectroscopy. The average crystal size was in the range of 10-26 nm. FTIR spectra show that the intensities of all impurity peaks get reduce with increasing annealing temperature. The band gap was determined from the diffuse reflectance (DR) spectra using the K-M function. The photoluminescence spectra were describe by well known \(\rm ^5D_0\)-\(\rm ^7F_j\) transitions \((J=0,1,2,3,4)\) of Eu\(^{3+}\) ions.
Keywords: XRD; FTIR; UV-VIS; PL; Nanophosphors